O33-1 Screening with low-dose computed tomography (ldct) of asbestos exposed subjects is associated with reduced lung cancer mortality. (1st September 2016) - Barbiero, Fabiano; Barbone, Fabio; Rosolen, Valentina; Giangreco, Manuela; Pisa, Federica Edith; Zanin, Tina; Meduri, Stefano; Cassetti, Paolo; Follador, Alessandro; Belvedere, Ornella; Grossi, Francesco; Fasola, Gianpiero
Abstract : Purpose: In 2002 subjects already enrolled in a surveillance program for asbestos-exposed workers were recruited in a Low Dose CT scan screening (LDCT) (ATOM002 Study). During the 2-year program LDCT identified 11 lung cancer (LC) cases versus none detected by chest radiographs (CXR). The objective of this study is to evaluate whether, after a 10-year follow-up, this program was effective in reducing mortality for LC as compared with conventional health surveillance. Methods: Within a cohort of 2, 433 occupationally asbestos-exposed men, enrolled in a public health surveillance program, we compared mortality and survival between participants in a screening program based on LDCT (ATOM002-P, n = 926) and non-participants (ATOM002-NP, n = 1, 507). For external comparison, we estimated the standardised mortality rate ratio (SMR_ITA) using italian standard rates. For internal comparisons we performed Cox proportional hazard models to assess survival for all causes, all cancers, LC and malignant neoplasm of the pleura. Final models were adjusted for smoking habits, age at start of follow-up, level of exposure to asbestos and Charlson-Quan comorbidity index. Results: LC crude mortality was 99.4 per 100, 000 person-year in ATOM002-P (Obs = 8) compared to 430.4 per 100, 000 person-year in ATOM002-NP (Obs = 50). Compared with italian mortality rates, a trend towards reduced mortality for lung cancer was found among ATOM002-P (SMR_ITA = 0.51 95% CI: 0.22–1.01), in contrast to a statistically significant increase in the ATOM002-NP (SMR_ITA = 1.98; 95% CI: 1.47–2.61). Internal comparisons show a significant 59% reduction in mortality for lung cancer in ATOM002 participants (HR = 0.41, 95% CI: 0.17–0.96). Mortality was also reduced for all causes (HR = 0.61, 95% CI: 0.44–0.84), but not for all cancers (HR = 0.97, 95% CI: 0.62–1.50) and malignant neoplasm of the pleura (HR = 0.86, 95% CI: 0.31–2.41). Conclusions: In our cohort, a 2-year LDCT-based screening protocol was more effective in reducing mortality for LC than conventional public health surveillance. Surveillance program for asbestos-exposed workers should include LDCT screening.